Utility of mitochondrial COI gene for identification of wild ungulate species of conservational importance from Pakistan. Issue 2 (2nd April 2020) - Naseem, Asif; Batool, Sajida; Abbas, Fakhar- i-
Abstract: Most of the ungulates of Pakistan are either threatened or endangered species and their solitary and inaccessible life style makes them difficult to study. Therefore, estimating biodiversity, monitoring illegal trades and detecting commercial food frauds involving these species is a challenge for zoologists and conservation biologists. Here, we have attempted to exploit the discriminating power of mitochondrial CO I gene to identify and to generate barcodes of the wild ungulate species of conservational importance found in Pakistan. 86 specimens of 19 wild ungulate species found in Pakistan were analyzed for their CO I sequences. This is the first generated molecular data for many of these endemic and nearly endemic species. Intra and interspecific distances revealed distinct barcode gap for each species and a Neighborhood-joining tree able to discriminate all species into their respective clades. In conclusion, mt CO I is a powerful discriminatory tool for the taxonomic classification of ungulates especially for species that are inaccessible and require noninvasive sampling.